The Knife of Never Letting Go: Chaos Walking Series #1 - Ness, Patrick, 1971- (Cambridge, Mass. : Candlewick Press, 2009)
Pursued by power-hungry Prentiss and mad minister Aaron, young Todd and Viola set out across New World searching for answers about his colony's true past and seeking a way to warn the ship bringing hopeful settlers from Old World.
Keywords: Social problems -- Fiction; Telepathy -- Fiction; Human-animal communication -- Fiction; Space colonies -- Fiction; Science fiction